SYSTEMATICS, TAXONOMY AND CLASSIFICATION OF BACTERIA - LYUDMILA A. Levanova; YULIYА V. Zakharova (Фундаментальная и клиническая медицина, 2017)
The lecture presents the recent advances in the taxonomy of microorganisms, the terminology, the principles, the rules, and the procedure for naming bacteria. In addition, we describe the differences between pro- and eukaryotes and between Archaea and Bacteria domains. Finally, we report the classification of bacteria relevant for basic, translational, and clinical medicine according to the 2nd edition of Bergey’s Manual of Systematic Bacteriology.